Australia's progress toward SDG4 targets for school-age students with disability - Stephen Hay; Wendi Beamish (Frontiers in Education)
Australia's progress toward achieving Sustainable Development Goal 4 (SDG4) for students with disability reveals both challenges and opportunities. Despite existing disability discrimination legislation, systemic barriers persist within government and non-government schooling sectors. A lack of a coordinated national strategy, combined with fragmented policies, has constrained efforts to promote inclusive education, leaving students with disability underserved, particularly in regional, rural, and remote areas. Underinvestment in mainstream schools has also created disparities in educational access and quality. Moreover, inadequate training of classroom teachers in these schools has continued to restrict the implementation of inclusive and individualized approaches, limiting educational outcomes for this student group. These students therefore continue to experience lower success and completion rates than their peers. This paper emphasizes the urgent need for systemic reforms, including targeted investments and a national policy framework aligned with SDG4, to address these issues. We argue that to achieve equitable, inclusive, and quality education for all students, collaborative effort across all levels of government and education sectors is required for Australia to realize sustainable progress toward its international commitments.